Correction: Choline alphoscerate: insights between acquired certainties and future perspectives - Biggio, Giovanni; Mencacci, Claudio (Frontiers in Aging Neuroscience, 2026)
Graphical AbstractDiagram illustrating the effects of choline alphoscerate on the brain. It highlights benefits like enhancement of cognitive functions and synaptic signaling. Key aspects include epigenetic regulation, acetylcholine neurotransmission, and membrane lipid composition. The diagram shows interactions with enzymes and neurotransmitters in the synaptic cleft, and includes references to Alzheimer's disease and healthy aging. Various compounds and neurotransmitters like acetylcholine, SAM, and Co-A are labeled, with processes such as the modulation of gene expression and enhancement of cholinergic tone noted. The image includes a legend for anti-cholinesterases.